Receptor Polymorphism and Genomic Structure Interact to Shape Bitter Taste Perception - Roudnitzky, Natacha; Behrens, Maik; Engel, Anika; Kohl, Susann; Thalmann, Sophie; Hübner, Sandra; Lossow, Kristina; Wooding, Stephen P; Meyerhof, Wolfgang (PLOS Genetics, 2015)
The ability to taste bitterness evolved to safeguard most animals, including humans, against potentially toxic substances, thereby leading to food rejection. Nonetheless, bitter perception is subject to individual variations due to the presence of genetic functional polymorphisms in bitter taste receptor (TAS2R) genes, such as the long-known association between genetic polymorphisms in TAS2R38 and bitter taste perception of phenylthiocarbamide. Yet, due to overlaps in specificities across receptors, such associations with a single TAS2R locus are uncommon. Therefore, to investigate more complex associations, we examined taste responses to six structurally diverse compounds (absinthin, amarogentin, cascarillin, grosheimin, quassin, and quinine) in a sample of the Caucasian population. By sequencing all bitter receptor loci, inferring long-range haplotypes, mapping their effects on phenotype variation, and characterizing functionally causal allelic variants, we deciphered at the molecular level how a subjects' genotype for the whole-family of TAS2R genes shapes variation in bitter taste perception. Within each haplotype block implicated in phenotypic variation, we provided evidence for at least one locus harboring functional polymorphic alleles, e.g. one locus for sensitivity to amarogentin, one of the most bitter natural compounds known, and two loci for sensitivity to grosheimin, one of the bitter compounds of artichoke. Our analyses revealed also, besides simple associations, complex associations of bitterness sensitivity across TAS2R loci. Indeed, even if several putative loci harbored both high- and low-sensitivity alleles, phenotypic variation depended on linkage between these alleles. When sensitive alleles for bitter compounds were maintained in the same linkage phase, genetically driven perceptual differences were obvious, e.g. for grosheimin. On the contrary, when sensitive alleles were in opposite phase, only weak genotype-phenotype associations were seen, e.g. for absinthin, the bitter principle of the beverage absinth. These findings illustrate the extent to which genetic influences on taste are complex, yet arise from both receptor activation patterns and linkage structure among receptor genes.